Policy-Driven Infrastructure Validation for Network Modernization - Kosaraju, Prasanth (International Journal of Computational and Experimental Science and Engineering, 2025)
Network infrastructure refresh projects traditionally focus on hardware replacement while neglecting the critical aspect of configuration standardization and policy enforcement, resulting in configuration inconsistencies and operational challenges that persist despite successful hardware upgrades. This article introduces NetConForm, a policy-based infrastructure standardization and validation framework designed specifically for large-scale network refresh initiatives that addresses the fundamental gap between hardware modernization and configuration standardization. The framework implements a comprehensive three-tier architecture consisting of a Policy Definition Layer that employs declarative baseline systems, a Validation Engine leveraging Python-based automation libraries for multi-vendor device interaction, and a Compliance Reporting System that maintains version-controlled repositories of configuration states. Through empirical evaluation across multiple enterprise network refresh projects, NetConForm demonstrates significant improvements in operational efficiency, compliance outcomes, and network reliability by transforming refresh projects from simple replacement exercises into opportunities for comprehensive infrastructure optimization. The framework's automated approach to configuration management, drawing from principles established in Infrastructure as Code and modern security configuration management practices, enables organizations to achieve systematic policy enforcement, proactive compliance validation, and continuous monitoring that aligns technical standards with business objectives and regulatory requirements.